KINETIC-CATALYTIC DETERMINATION OF ULTRAMICRO AMOUNTS OF Co(II) USING 4-HYDROXYCOUMARINE-PERMANGANATE REDOX REACTION - Sejmanović, Dragana; Micić, Ružica; Simonović, Ranko (Bulletin of Natural Sciences Research, 2018)
Determination of Co(II) based on its catalytic effect on the reaction between 4-hydroxycoumarine and potassium permanganate,  in the presence of acetate buffer was described. The method development includes optimization of the reagent concentration and temperature. Absorbance of potassium permanganate was measured at 525 nm. The calibration curve was linear in the range of 0.5 - 4 ng/cm3 of Co(II). The relative standard deviation was in the interval 6.25-2.60 % of the concentration range of 0.6-3 ng/cm3 Co(II), respectively. The interference effects of foreign ions were determined for the assessment of the selectivity of the method. The proposed method was found to have excellent sensitivity, relatively good selectivity and simplicity.
Keywords: cobalt(II); kinetic method; 4-hydroxycoumarine